Towards Legality and Affect - Christ, Birte; Schniedermann, Wibke; Justus Liebig University Giessen (My University, 2024)
The contributions to this special issue on “Towards Legality and Affect” engage with Greta Olson’s recent challenges to the discipline of Law and Literature in From Law and Literature to Legality and Affect (Oxford UP 2022). They grapple with Olson’s reconceptualization of legality and her emphasis on the role of affect by way of case studies that include diverse media and transnational perspectives.
Keywords: ddc:820